Clinical Outcomes of Endoscopic Resection for Low-Grade Dysplasia and High-Grade Dysplasia on Gastric Pretreatment Biopsy: Korea ESD Study Group - Jeon, Jung Won (Gut Liver, 2021)
BACKGROUND/AIMS: Some cases of gastric low-grade dysplasia (LGD) and high-grade dysplasia (HGD) on forceps biopsy (FB) are diagnosed as gastric cancer (GC) after endoscopic resection (ER). This study aims to evaluate the clinical outcomes of ER for gastric LGD and HGD on pretreatment FB and to identify the factors that predict pathologic upstaging to GC. METHODS: Patients who underwent ER for LGD and HGD on pretreatment FB from March 2005 to February 2018 in 14 hospitals in South Korea were enrolled, and the patients’ medical records were reviewed retrospectively. RESULTS: This study included 2,150 cases of LGD and 1,534 cases of HGD diagnosed by pretreatment FB. In total, 589 of 2,150 LGDs (27.4%) were diagnosed as GC after ER. Helicobacter pylori infection, smoking history, tumor location in the lower third of the stomach, tumor size >10 mm, depressed lesion, and ulceration significantly predicted GC. A total of 1,115 out of 1,534 HGDs (72.7%) were diagnosed with GC after ER. Previous history of GC, H. pylori infection, smoking history, tumor location in the lower third of the stomach, tumor size >10 mm, depressed lesion, and ulceration were significantly associated with GC. As the number of risk factors predicting GC increased in both LGD and HGD on pretreatment FB, the rate of upstaging to GC after ER increased. CONCLUSIONS: A substantial proportion of LGDs and HGDs on pretreatment FB were diagnosed as GC after ER. Accurate ER procedures such as endoscopic submucosal dissection should be recommended in cases of LGD and HGD with factors predicting pathologic upstaging to GC.